Dong Thap university journal of science: Natural sciences issue (Dong Thap University, 2024)
Content: Predicting learning status of informatics students at Dong Thap University based on machine learning models ; Studying the distribution of L-citrulline in watermelon fruits at different storage conditions ; Identification of the potential compounds for inhibition CD44 target of human breast cancer stem cells by docking method ...